Analysis Of Job Training, Motivation, Career Development, Discipline And Job Stress On Employee Performance Of Pt Tarindo Kuningan Juwana - Septian, Erfin; Efriyani Sumastuti,; Rita Meiriyanti, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract This research aims to determine the effect of job training, motivation, career development, discipline and work stress on the performance of PT employees. Tarindo Kuningan Juwana. The method used is quantitative through distributing questionnaires. The total sample was 223 respondents using random sampling technique. This research method uses a questionnaire and data analysis using SPSS which includes tests of validity, reliability, classical assumptions, normality, heteroscedasticity, multicollinearity and multiple linear analysis. The results of this research are that job training, motivation, career development and discipline influence employee performance, while work stress does not influence the performance of PT employees. Tarindo Kuningan Juwana.